The Influence of Good Governance and Work Discipline on The Performance of Employees: JEL Classification: J24, M12, M54, H83, D73 - Lukmansyah, Lukmansyah; Yunus, Mujahid; Wahyu, Wahyu (Journal La Bisecoman, 2025)
This study aims to determine and analyze the influence of good governance and work discipline on the performance of employees at the South Nunukan District Office. This study used a quantitative method with multiple linear regression data analysis using SPSS software. The primary data were collected from all 95 employees, both civil servants (ASN) and honorary employees. The results show that simultaneously, good governance and work discipline significantly influence employee performance. This indicates that the combination of good governance and a disciplined work culture is crucial in driving effective public service.